Factors affecting readiness toward online learning among medical students during COVID-19 pandemic in Indonesia - Rony Wiranto; Rizma Adlia Syakurah (Institute of Advanced Engineering and Science, 2022)
The rapid spread of transmission COVID-19 leads to the government applied a regulation to close schools and colleges for a while, as an effort to stop the spread. It also has an impact on medical student education that can be threatened by their educational system. This study identified and analyzed the factors affecting the readiness of medical students for studying online during the COVID-19 pandemic. This was an observational analytic study with a cross-sectional approach. A total of 3,331 respondents from all over Indonesia participated in this study. An online questionnaire by Indonesian Medical Student Senate Association (Ikatan Senat Mahasiswa Kedokteran Indonesia/ISMKI) was used and distributed from April 9th, 2020 to June 21st, 2020. A Chi-square test (alternative: Fisher exact test) and logistic regression with significance alpha=0.05 used to analyze. The university origin (p=0.031, OR=1.130 (1.012–1.263)), internet connections (p=0.001, OR=1.387 (1.134–1.696)), and learning interaction models (p<0.000, OR=0.463 (0.384–0.558)) were affected medical students’ readiness for online learning.